Comparative Analytical Studies of Crystalline and Noncrystalline Limestone of Bihar - Kamal, K.P.; Mujtaba, S.G.; Mustafa Siddiqui, Khalid (Asian Journal of Chemistry, 2012)
Limestone is an important raw material chemically known as a double carbonate of calcium and magnesium. There are two types of limestone found in Bihar. The first is the non-crystalline variety, whose origin is sedimentary. It is found in Rohtas area of Bihar in huge amount. The crystalline variety is of different nature. It has got a crystalline shape. It is found in Hazaribag, Ranchi and Palamau Districts. According to geochemistry it is believed that crystalline limestone is a product of alteration of basic rocks. These basic rocks are dark colored, hard and contain muscowhite, biotite, horn blende and quartz. These basic rocks are host country rocks and it is believed that crystalline limestone of these areas is an alteration product of the same due to high grade metamorphism. However a comparative analytical study has been carried out in this paper to throw light on the genesis of these two types of limestone. Moreover, the limestone of Hazaribag is not used extensively. The utilization aspect shall also be studied here.